Mineral rents and social development in Norway - Halvor Mehlum; Karl Ove Moene; Ragnar Torvik (University of Oslo, Department of Economics, 2011)
Norway is often referred to as the prime example of a country that has achieved high growth and low income inequality despite its vast natural resources. This contrasts sharply with many other resource abundant countries, which raises the questions why Norway has succeeded while many other resource abundant countries have not. That is the topic of this paper. To make progress we first need to find out along which dimensions Norway differs from resource abundant countries with a less favorable development. Thereafter we turn to a more detailed description and investigation of the policies adopted in Norway, and discuss if there are lessons to be learned for other resource abundant countries.
Keywords: E6; E61; O13; Q32; Q38; 330; Sovereign wealth fund; Norway; multi-sector growth; labor supply